PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA YANG MENGAKIBATKAN KEMATIAN SESEORANG - Sawaluddin Siregar; Putra Halomoan (Yurisprudentia: Jurnal Hukum Ekonomi, 2022)
Violent crime is a form of intentional action that causes a person's health / soul to change for the worse, in carrying out violence the perpetrator will make physical contact in the form of beating someone, causing a person to cause bruises in the form of wounds or the onset of pain in the victim's body. , violence generally occurs due to a dispute that has not been completed or someone feels belittled/demeaned by others so that the occurrence of revenge which ultimately leads to violent crime, in this thesis the author raises the issue of violent crime in imposing a criminal offense against perpetrators of domestic violence. District Court Decision Number 389/pid.B/2021/PN.Andada, The purpose of the problem is to find out the legal provisions referred to as violent crimes that cause a person to die and to determine the accountability In addition to the judge's considerations and the factors causing the occurrence of violent crimes against victims of violent crimes that caused injuries, the case number is State Number 389/pid.B/2021/PN. Kalianda